DETERMINATION OF METHYLPARABEN IN COSMETICS BY HPLC METHOD (Scientific journal of the Fergana State University, 2023)
Methylparaben is used in cosmetics as an antimicrobial preservative. Overdose of methylparaben can lead to dermatitis and drug sensitivity. A fast and effective method for determining the concentration of parabens has been developed - the method of high performance liquid chromatography. Supelco C18, 150x4.6mm (5 μm) and BDS Hypersil C8 150x4.6 mm (5 μm) columns were used to separate methylparaben. The high absorption spectrum of methylparaben is 254 nm. The creams were extracted in an acetonitrile solution in an ultrasonic bath for 15 min. The results showed that  the content of methylparaben in cosmetic creams was   determined  quickly and effitciently  in according  to the State Standard.